Výskyt obezity a jejích komplikací v Ceské republice - Matoulek, M; Svacina, S; Lajka, J (Vnitrni lekarstvi, 2010)
Over the recent years, the incidence of obesity is continuously rising. A research conducted in 2008-2009 on a representative sample of Czech population (n = 2,058) suggests that 23% of adult population of the Czech Republic are obese and 34% are overweight. This represents an increase of 5% in the number of obese people (17% vs. 22%), while the number of overweight remains practically the same (35% vs. 34%). A more significant shift in female waist circumference compared to male has also been shown. The incidence of hypertension in the evaluated sample was more than a two-fold higher in obese participants (48% vs. 21%) and as much as 3-fold higher in type 2 diabetes mellitus (7% vs. 20%). The risk of body weight increase is the highest between 50th and 59th year of age, where hypertension and diabetes are the most frequently diagnosed. The risk of obesity in adulthood is mostly carried over from childhood and more than 3/4 (77%) of those, who were overweight or obese as children, are in these categories as adults. Quality of life and satisfaction with own health is more related to BMI than age. Even though body weigh is increasing with the same amplitude in sportsman and physically active people, they are reaching lower final BMI due to their lower starting body weight. It is clear that physically active lifestyle in younger age is the best predictor of lower BMI in adult life. Consumption of secondary processed meat and lower consumption of fruit and vegetables are important factors in adulthood.
Keywords: dospělí; Female; Adult; mladý dospělý; ženské pohlaví; Life Style; životní styl; Obesity; lidé; Incidence; obezita; Male; incidence; Czech Republic; Young Adult; index tělesné hmotnosti; Česká republika; lidé středního věku; mužské pohlaví; Body Mass Index; Middle Aged; Humans